2011
DOI: 10.4306/pi.2011.8.3.214
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Fertility and Fecundity among Patients with Bipolar I Disorder and Schizophrenia in Egypt

Abstract: ObjectiveTo evaluate reproduction among patients with bipolar I disorder (BP1) or schizophrenia (SZ) in Egypt.MethodsBP1 patients (n=113) were compared with community based, demographically balanced controls (n=124) and SZ patients (n=79, DSM-IV). All participants were evaluated using structured interviews and corroborative data were obtained from relatives. Standard indices of procreation were included in multivariate analyses that incorporated key demographic variables.ResultsControl individuals were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…This finding supports the robust evidence in the literature, which suggests that schizophrenia strongly aggregates in families of schizophrenia probands more than the general population. 18,24 It also supports the views of previous authors that the risk in relatives is a function of the degree of genetic relatedness to the probands and the comparison group. 24,25 Thus, the highest risk was amongst the FDRs followed by second- and third-degree relatives, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…This finding supports the robust evidence in the literature, which suggests that schizophrenia strongly aggregates in families of schizophrenia probands more than the general population. 18,24 It also supports the views of previous authors that the risk in relatives is a function of the degree of genetic relatedness to the probands and the comparison group. 24,25 Thus, the highest risk was amongst the FDRs followed by second- and third-degree relatives, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…[ 44 ] Studies from other countries have also shown lesser number of conceptions and live children for women with BD compared to general populations and major depressive disorder. [ 39 45 ] However, when compared to patients of schizophrenia, findings are inconsistent, with some studies showing lesser number of conceptions and live children for women with BD,[ 39 ] whereas others have reported comparable rates. [ 45 ]…”
Section: Bipolar Affective Disorder and Procreationmentioning
confidence: 99%
“…[ 39 45 ] However, when compared to patients of schizophrenia, findings are inconsistent, with some studies showing lesser number of conceptions and live children for women with BD,[ 39 ] whereas others have reported comparable rates. [ 45 ]…”
Section: Bipolar Affective Disorder and Procreationmentioning
confidence: 99%
“…An interesting, though not unexpected, observation is that patients with schizophrenia have significantly fewer children compared to the general population [17, 18, 19]. In theory, this should be generating an enormous negative selective pressure quickly removing risk alleles from the population; however, the disease maintains a relatively high heritability and prevalence at ∼1%.…”
Section: Introductionmentioning
confidence: 99%